Assessment of piscicidal effect of five toxicants for the eradication of weed fish Nile tilapia (Oreochromis niloticus) - Aman, S; Aftab, B; Ahmad, S (Journal of the Hellenic Veterinary Medical Society, 2023)
Unwanted or weed fish in aquaculture pond may affect the growth and development of cultured fish species. The current investigation aimed to assess the piscicidal effect of five commercial toxicants on weed fish, Nile tilapia (Oreochromis niloticus) for a short period. The fish was exposed to four concentrations (0.5, 1.0, 1.5, and 2.0 ppm) of dimethoate, pyrethroid lambda-cyhalothrin, cypermethrin, malathion, and Chillas along with control (without any toxicants) during a 48-hour static bioassay. Fish mortality and physicochemical parameters i.e., pH and dissolved oxygen (DO) of water were checked after every 8 hours. The pH of water varied from 3.46to 6.5 and DO range 2.70- 5.66 during all experiments. After 48 hours of exposure, the maximum fish mortality was achieved by dimethoate (4.15, 8.30%), cypermethrin (4.16, 8.32%), malathion (4.0, 8.00%), and Chillas (4.0, 8.00%) at the highest applied concentration (2.0 ppm). While pyrethroid lambda-cyhalothrin showed the highest mortality at 1.5 ppm (4.16) with 8.32% as well as on 2.0 ppm (4.16, 8.32%). In conclusion, pyrethroid lambda-cyhalothrin was observed as the best toxicant as piscicide causing overall higher mortality on all applied concentrations. However, the long-term experiment is further needed to clarify the mortality trend and optimization of toxicants in a long-term experiment.